A preclinical screen to evaluate pharmacotherapies for the treatment of agitation in dementia. Issue 2 (April 2017) - O'Hare, Eugene; Page, Deaglan; Curran, William; Hong, Jeong-Sup; Kim, Eun-Mee
Abstract : Agitation associated with dementia is frequently reported clinically but has received little attention in preclinical models of dementia. The current study used a 7PA2 CM intracerebroventricular injection model of Alzheimer's disease (AD) to assess acute memory impairment, and a bilateral intrahippocampal (IH) injection model of AD (aggregated Aβ1–42 injections) and a bilateral IH injection model of dementia with Lewy bodies (aggregated NAC61–95 injections) to assess chronic memory impairment in the rat. An alternating-lever cyclic-ratio schedule of operant responding was used for data collection, where incorrect lever perseverations measured executive function (memory) and running response rates (RRR) measured behavioral output (agitation). The results indicate that bilateral IH injections of Aβ1–42 and bilateral IH injections of NAC61–95 decreased memory function and increased RRRs, whereas intracerebroventricular injections of 7PA2 CM decreased memory function but did not increase RRRs. These findings show that using the aggregated peptide IH injection models of dementia to induce chronic neurotoxicity, memory decline was accompanied by elevated behavioral output. This demonstrates that IH peptide injection models of dementia provide a preclinical screen for pharmacological interventions used in the treatment of increased behavioral output (agitation), which also establish detrimental side effects on memory.